2015
DOI: 10.3390/molecules201119737
|View full text |Cite
|
Sign up to set email alerts
|

Carapanolides T–X from Carapa guianensis (Andiroba) Seeds

Abstract: Abstract:Two new mexicanolide-type limonoids, carapanolides T-U (1-2), and three new phragmalin-type limonoids, carapanolides V-X (3-5), were isolated from the seeds of Carapa guianensis (andiroba). Their structures were determined on the basis of 1D-and 2D-NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…Extracts of the bark, flowers, and seeds have been used for centuries by the Amazonian people and exhibit various effects: anti-bacterial [ 4 ], anti-cancerous [ 5 ], anti-tumor [ 6 ], anti-fungal [ 6 ], insect repellent [ 7 ], analgesic [ 8 ], anti-malarial [ 9 ], anti-inflammatory [ 10 ], antiallergic [ 11 ], and anti-plasmoidal effects [ 12 ], as well as acute and subacute toxicity [ 13 ]. In the course of our studies on the chemical constituents from C. guianensis ( Carapa guianensis ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], we have isolated several limonoids, including andirolides A–Y from the flower oil [ 14 , 15 , 16 , 17 ], carapanolides A–X [ 18 , 19 , 20 , 21 , 22 ], and guianolides A and B [ 23 ] from the seed oil. We have also reported that several limonoids from C. guianensis showed cytotoxic [ 14 , 16 , 18 , 19 , 23 ], antimalarial [ 15 ], anti-inflammatory [ 17 , 20 , 22 ], and triglyceride metabolism-promoting activities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of the bark, flowers, and seeds have been used for centuries by the Amazonian people and exhibit various effects: anti-bacterial [ 4 ], anti-cancerous [ 5 ], anti-tumor [ 6 ], anti-fungal [ 6 ], insect repellent [ 7 ], analgesic [ 8 ], anti-malarial [ 9 ], anti-inflammatory [ 10 ], antiallergic [ 11 ], and anti-plasmoidal effects [ 12 ], as well as acute and subacute toxicity [ 13 ]. In the course of our studies on the chemical constituents from C. guianensis ( Carapa guianensis ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], we have isolated several limonoids, including andirolides A–Y from the flower oil [ 14 , 15 , 16 , 17 ], carapanolides A–X [ 18 , 19 , 20 , 21 , 22 ], and guianolides A and B [ 23 ] from the seed oil. We have also reported that several limonoids from C. guianensis showed cytotoxic [ 14 , 16 , 18 , 19 , 23 ], antimalarial [ 15 ], anti-inflammatory [ 17 , 20 , 22 ], and triglyceride metabolism-promoting activities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…No que tange suas propriedades antiparasíticas, o óleo da C. guianensis demostrou caráter protetivo a partir da presença de limonóides no seu óleo 9,10 . No que tange a sua bioquímica, tal classe de substância tem a sua efetividade anti-parasitária atribuída a presença de tetranortriterpenóides, de modo que os principais exemplos encontrados na andiroba são o 6α-acetoxygedunin, 7-deacetoxi-7-oxogedunin, andirobin, gedunin, metil-angolensate e caraponolideos C-I, T-U e V-X [11][12][13] .…”
Section: Introductionunclassified
“…Among the limonoids found in C. guianensis seed oil are 6 α -acetoxygedunin, 7-deacetoxy-7-oxogedunin, andirobin, gedunin and methyl-angolensate [ 12 ], guianolides A and B, [ 13 ], carapanolides M–S [ 14 ], carapanolides C–I [ 15 ], carapanolides T-U, and carapanolides V-X [ 16 ].…”
Section: Introductionmentioning
confidence: 99%